COMMON FIXED POINT THEOREM IN INTUITIONITIC FUZZY METRIC SPACES (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Fixed point is an important branch of analysis to enhance its literature the prime .The object of this paper is to prove the common fixed point theorems for six self mapping taking the pair of maps as coincidentally commutating and compatible in an intuitionistic Fuzzy Metric Space. Our result is an extended and generalized result of Kumar et al.[11]